A föderalizmus pozíciói a Nagy Háború korában: a lengyel trializmus versus dualizmus kérdése az osztrák és magyar politikában 1914–1918 = Federalism during the Great War: trialism versus dualism with Poland in the Austro-Hungarian politics 1914–1918 - Gyarmati, Enikő (Közép-Európai Közlemények, 2018)
The autonomy of historical Poland as an independent state for the Triple Entente respectively as a self-dependent state for the Central Powers became a political objective during the Great War. The German Empire was interested first of all in a buffer state and integrating Poland economically into Middle Europe, while in the Austro-Hungarian Monarchy the Austro-Hungarian-Polish trialism as well the Austro-Polish dualism had been under consideration after the military successes in the Eastern Front in the middle of 1915. The present study highlights the pros and cons of the conceptions, discussed on the Cabinet meetings held October 2nd in Budapest and October 6th 1915 in Vienna. In spite of the fact, that the Hungarian Prime Minister Count István Tisza had not supported the idea of an Austro-Hungarian-Polish trialism and required substantial territorial compensations (the integration of Bosnia-Hercegowina, Dalmatia into the Hungarian Kingdom, a small territorial compensation around Fiume), and financial compensations (burdening Austro-Hungarian debts onto Poland, reduction of the financial quotas for the Hungarian Kingdom), all these compensations for accepting the Austro-Polish dualistic solution, he offered at the same time substantial support for the Austro-German politicans, who also rejected any constitutional modification of Austro-Hungarian Dualism. The destiny of Poland after the Great War lied in the hands of the Allies’ politicans and as a result an independent Poland had been established instead of the alternatives of integration models into Austria-Hungary or the German Empire.